Manajemen Metadata: Solusi Untuk Tantangan Data di Era Informasi - Batubara, Alwi Ardiansyah Putra; Nasution, Muhammad Irwan Padli (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
In an information age characterized by rapid data growth, metadata management has become critical to ensure the accessibility, regularity, and efficient utilization of data. This article discusses the key challenges that organizations face in data management, including issues of integration, data quality, and information security. By establishing a comprehensive metadata management framework, organizations can address these challenges through standardization, organization, and storage of information. In addition, this study investigates the various tools and technologies that can be applied to improve metadata management, as well as their impact on decision-making and innovation. The findings of this study indicate that implementing good metadata management not only improves operational efficiency but also provides a competitive advantage in an increasingly digital marketplace.